Four MicroRNAs, miR-13b-3p, miR-278-5p, miR-10483-5p, and miR-10485-5p, Mediate Insecticide Tolerance in Spodoptera frugiperda - Yang, Yuanxue; Zhang, Yun; Wang, Aiyu; Duan, Ailing; Xue, Chao; Wang, Kaiyun; Zhao, Ming; Zhang, Jianhua (Frontiers in Genetics, 2022)
Spodoptera frugiperda is the world’s major agricultural pests, and has the distinctive features of high fecundity, strong migratory capacity and high resistance to most insecticides. At present, the control of S. frugiperda in China relies mainly on the spraying of chemical insecticides. MicroRNAs (miRNAs) are a class of small, single-stranded, non-coding RNAs, and play crucial regulatory roles in various physiological processes, including the insecticide resistance in insects. However, little is known about the regulatory roles of miRNAs on the resistance of S. frugiperda to insecticides. In the present research, the miRNAs that were differentially expressed after cyantraniliprole, spinetoram and emamectin benzoate treatment were analyzed by RNA-Seq. A total of 504 miRNAs were systematically identified from S. frugiperda, and 24, 22 and 31 miRNAs were differentially expressed after treatments of cyantraniliprole, spinetoram and emamectin benzoate. GO and KEGG enrichment analyses were used to predict the function of differentially expressed miRNAs’ target genes. Importantly, ten miRNAs were significantly differentially expressed among the treatments of three insecticides. MiR-278-5p, miR-13b-3p, miR-10485-5p and miR-10483-5p were significantly down-regulated among the treatments of three insecticides by RT-qPCR. Furthermore, overexpression of miR-278-5p, miR-13b-3p, miR-10485-5p and miR-10483-5p significantly increased the mortality of S. frugiperda to cyantraniliprole and emamectin benzoate. The mortality was significantly increased with spinetoram treatment after overexpression of miR-13b-3p, miR-10485-5p and miR-10483-5p. These results suggest that miRNAs, which are differentially expressed in response to insecticides, may play a key regulatory role in the insecticide tolerance in S. frugiperda.